Resolução simultânea do problema de leiaute de facilidades e roteamento de fluxo por meio de uma abordagem exata - Juliano Henrique Silva (2012)
The placement of the processors resources in a facility directly impacts the level of service. The Facility Layout Problem is a combinatorial optimization problem which is concerned in determining the position of the resources to minimize the cost of moving goods within the factory. In volatile environments, the Distributed Layout has been highlighted because it posses features that help companies cope with the uctuations present in these environments. Traditionally, the models proposed by the authors to solve this problem are nonlinear, in particular, are derived from the quadratic assignment model. The aim of this paper is to propose a linear model that solves the Distributed Layout Problem. By having a special structure in their formulation, the model was solved by the Benders decomposition method added the following procedures hot start, core-point and Benders-and-Cut. Based on the computational experiments, noted however, a better performance of the software CPLEX compared to the implemented procedure.